The Influence of Lecturer Competence, Work Motivation, and Organizational Commitment on Leadership in Higher Education in Banyuwangi Regency - Haya Haya (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze the influence of lecturer competence, work motivation, and organizational commitment on leadership in universities in Banyuwangi Regency. The research uses a quantitative approach with an explanatory method. Data was collected from permanent lecturers of universities using questionnaires and analyzed with SEM-PLS through SmartPLS 3. The results of the study showed that lecturer competence had a positive effect on leadership, work motivation had a negative effect, while organizational commitment had the greatest positive influence. The R-Square value of 0.356 indicates that all three variables explain 35.6% of the leadership variation. These findings recommend increasing organizational commitment and lecturer competencies to strengthen leadership in higher education.